2020
DOI: 10.3389/fped.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Managing Ureteropelvic Junction Obstruction in the Young Infant

Abstract: In the last decade, management of congenital UPJ obstruction has become progressively observational despite the lack of precise predictors of outcome. While it is clear that many children will have resolution of their hydronephrosis and healthy kidneys, it is equally clear that there are those in whom renal functional development is at risk. Surgical intervention for the young infant, under 6 months, has become relatively infrequent, yet can be necessary and poses unique challenges. This review will address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 92 publications
0
38
0
1
Order By: Relevance
“…Since hydronephrosis is a common finding in prenatal ultrasound, and even if imaging techniques successfully detect asymptomatic cases, the emergent question of progression to severe renal impairment remains crucial for pediatric patient stratification and management [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since hydronephrosis is a common finding in prenatal ultrasound, and even if imaging techniques successfully detect asymptomatic cases, the emergent question of progression to severe renal impairment remains crucial for pediatric patient stratification and management [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive hydronephrosis, predominantly arising from UPJO, may result in chronic kidney disease (CKD) in children [ 25 ]. Longstanding complications of renal damage may appear later, in young adulthood, and by that time, noxious effects of renal development could have happened [ 7 ]. The modern era of minimally invasive approaches intensifies the need to discover reliable and sensitive diagnostic and prognostic biomarkers for the most effective and refined treatment of UPJO patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While current literature indicates that a large proportion of cases are stabilized or resolved following conservative management [ 1 , 3 , 6 ], studies have reported differing findings regarding the proportion of patients who go on to require surgery. A recent review found that the rate of complete resolution of prenatally-detected HN in the absence of surgery may range from 33 to 70% [ 7 ]. Discrepancies in the rates of patients who require surgery may be largely due to differences in HN severity between populations [ 8 – 13 ].…”
Section: Introductionmentioning
confidence: 99%